Interdependent Preferences for Financing and Providing Public Goods—The Case of National Defense - Armin~A. Bolouri; Tim Lohse; Salmai Qari (Kyklos, 2025)
Governments often choose deficit financing over budget cuts or tax increases to fund public goods, driven by the political unpopularity of the latter options. This study investigates the potential trade-off between maintaining prudent public finances and securing voter support by analyzing the relationship between preferences for the provision and financing of public goods. We use a survey-based discrete choice experiment with 1808 respondents representative of the German population. Focusing on national defense as a case study, our findings reveal a strong interdependence between spending and financing preferences: individuals who highly value defense readiness and are aware of its costs tend to support deficit-neutral budgeting, favoring tax increases to finance budget expansions. Conversely, those less supportive of defense expenditure prefer debt issuance and budget consolidation, avoiding immediate cost-bearing. Additionally, preferences vary by political and sociodemographic characteristics. These results indicate that citizens' preferences are interdependent, influenced by both revenues and expenditures in the public budget. Moreover, they suggest that prudent fiscal policies aligned with public support—such as tax-based financing for defense—may be politically feasible. Policymakers can leverage these insights to design fiscal strategies that reflect voter priorities, thereby reducing the risk of electoral backlash and promoting sustainable public finances.
Keywords: 300; financing public goods; national defense; nonmarket valuation; policy preferences; public good provision